The incidence and body site of skin cancers in the population groups of Astana, Kazakhstan. Issue 7 (31st May 2018) - McLoone, Pauline; McLoone, Philip; Imanbayev, Khalel; Norval, Mary
Abstract: Background and aims: Data on cutaneous malignant melanoma (CMM), squamous cell carcinoma of the skin (SCC), and basal cell carcinoma (BCC) in populations consisting of multi‐racial groups in the Commonwealth of Independent States are limited. Here, the main aim was to analyse the incidence and body site of these cancers in the population groups of Astana, Kazakhstan (2007‐2016). Methods: Annual age standardised incidences and body sites of BCC, SCC, and CMM in Astana's population, divided into "Kazakhs and other Turkic/Asian" and "Russian and other European/Caucasian" groups, were calculated from histologically confirmed cases reported to Astana Oncology Centre. Results: During the period January 2007 to October 2016, 647 skin cancers were diagnosed. The age and sex standardised incidence of BCC, SCC, and CMM increased significantly between 2007 to 2011 and 2012 to 2016. Higher incidences occurred in the Russian and other European/Caucasian group compared with the Kazakh and other Turkic/Asian group for the 3 skin cancers. BCC was the most common type of skin tumour, followed by SCC, and then CMM, in both population groups and sexes. The head/neck was the commonest site for BCC and SCC in all groups. For CMM, the most frequent site was the trunk in the Russian group and the head/neck in the Kazakh group. Conclusion: The incidence of skin tumours in Astana rose over the past 10 years. Differences in skin phototypes and sun exposure/ protection behaviours may account for the more frequent occurrence of skin tumours in the Russian population group compared with the Kazakh population group. Abstract : Background and aims: Data on cutaneous malignant melanoma (CMM), squamous cell carcinoma of the skin (SCC), and basal cell carcinoma (BCC) in populations consisting of multi‐racial groups in the Commonwealth of Independent States are limited. Here, the main aim was to analyse the incidence and body site of these cancers in the population groups of Astana, Kazakhstan (2007‐2016). Methods: Annual age standardised incidences and body sites of BCC, SCC, and CMM in Astana's population, divided into "Kazakhs and other Turkic/Asian" and "Russian and other European/Caucasian" groups, were calculated from histologically confirmed cases reported to Astana Oncology Centre. Results: During the period January 2007 to October 2016, 647 skin cancers were diagnosed. The age and sex standardised incidence of BCC, SCC, and CMM increased significantly between 2007 to 2011 and 2012 to 2016. Higher incidences occurred in the Russian and other European/Caucasian group compared with the Kazakh and other Turkic/Asian group for the 3 skin cancers. BCC was the most common type of skin tumour, followed by SCC, and then CMM, in both population groups and sexes. The head/neck was the commonest site for BCC and SCC in all groups. For CMM, the most frequent site was the trunk in the Russian group and the head/neck in the Kazakh group. Conclusion: The incidence of skin tumours in Astana rose over the past 10 years. Differences in skin phototypes and sun exposure/ protection behaviours may account for the more frequent occurrence of skin tumours in the Russian population group compared with the Kazakh population group.